Prinsip Kejujuran Dalam Perdagangan Versi Islam - Muhammad Nizar (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2018)
The concept of trading in Islam must be based on the values ​​and ethics derived from the basic values ​​that uphold the religion of honesty and fairness. Prophet has laid the basic principles of how the implementation of fair trade and honest. The basic principles laid down by the Prophet is related to market mechanisms in trade, in which both sides can sell and buy items outright that there is no interference and intervention of other parties in determining the price of goods. With the honesty expected of a Muslim trading business will be more advanced and developed, as will be blessed by Allah in this world and in the hereafter.